Bilateral Sensory Changes and High Burden of Disease in Patients With Chronic Pain and Unilateral Nondermatomal Somatosensory Deficits: A Quantitative Sensory Testing and Clinical Study. Issue 8 (August 2017) - Landmann, Gunther; Dumat, Wolfgang; Egloff, Niklaus; Gantenbein, Andreas R.; Matter, Sibylle; Pirotta, Roberto; Sándor, Peter S.; Schleinzer, Wolfgang; Seifert, Burkhardt; Sprott, Haiko; Stockinger, Lenka; Riederer, Franz
Abstract : Objectives: Widespread sensory deficits resembling hemihypoesthesia occur in 20% to 40% of chronic pain patients on the side of pain, independent of pain etiology, and have been termed nondermatomal sensory deficits (NDSDs). Sensory profiles have rarely been investigated in NDSDs. Materials and Methods: Quantitative sensory testing according to the protocol of the German Research Network on Neuropathic Pain (DFNS) was performed in the face, hand, and foot of the painful body side and in contralateral regions in chronic pain patients. Twenty-five patients with NDSDs and 23 without NDSDs (termed the pain-only group) were included after exclusion of neuropathic pain. Comprehensive clinical and psychiatric evaluations were carried out. Results: NDSD in chronic pain was associated with high burden of disease and more widespread pain. Only in the NDSD group were significantly higher thresholds for mechanical and painful stimuli found in at least 2 of 3 regions ipsilateral to pain. In addition, we found a bilateral loss of function for temperature and vibration detection, and a gain of function for pressure pain in certain regions in patients with NDSD. Sensory loss and gain of function for pressure pain correlated with pain intensity in several regions. Discussion: This may indicate a distinct sensory profile in chronic non-neuropathic pain and NDSD, probably attributable to altered central pain processing and sensitization. The presence of NDSD in chronic non-neuropathic pain may be regarded as a marker for higher burden of pain disease. Abstract : Supplemental Digital Content is available in the text.